The failure of indigenous settlements in the Captaincy of Goiás - Nascimento, PatríciaEmanuelle; Nazareno, Elias; Baines, Stephen Grant (Diálogos Latinoamericanos, 2023)
In this article, we address an unprecedented discussion about the indigenous settlements in the Captaincy of Goiás, a Midwestern state of Brazil. It is an analysis of the failure of these colonial spaces, analyzed from a decolonial perspective which draws attention to indigenous strategies and actions as a relevant factor for such an unfolding. As the many years of coloniality have promoted a silencing of indigenous decolonial actions, there is a need to rewrite the history of contact relations in order to repair invisibilities and highlight the various forms of indigenous actions taken. The methodological-theoretical framework used here is based on the Latin American school of thought Modernity/Coloniality.